THREE MAJOR FACTORS THAT CAUSE DIVORCE AND ITS SOLUTION IN ISLAM: A Case Study at Majalengka Religious Court in 2014 - 2017 - Administrator, Journal (AL-MASHALIH (Journal of Islamic Law), 2018)
This study aims to determine the factors causing divorce and to obtain the representation as well as obstacles encountered in the litigation, the settlement of divorce cases in Majalengka Religious Court happened in 2014 - 2017. The type of research used in this study is qualitative research using ethnography method because it is carried out in natural condition and it is cultural. The researcher comes directly to Majalengka regency data source and divorce lawsuit so that here the researcher is the key instrument. The result of the study, based on the data taken from 2014 – 2017, reveals that the three major factors causing divorce happened in Majalengka regency are: (1) leaving the obligations (69.20%), (2) Continuous disputes (22.12%), and (3) moral problems (7.45%). Thus, it can be concluded that the most divorce case happened in Majalengka Religious Court is because of leaving the obligation and not fulfilling the rights of the spouse. In particular, divorce factors in Majalengka include (1) economics, (2) irresponsibility, (3) unharmony, (4) third party interference, (5) jealousy and (6) moral crisis. A solution proposed by Imam Nawawi Al-Bantani to overcome the divorce is by fulfilling the rights and obligations of each. The rights of a wife and obligations of a husband are: (1) getting good treatment, (2) earning a living, (3) getting dowry, and (4) getting education. Four kinds of husband's rights and wife’s obligations are: (1) getting obedience, (2) getting good behavior, (3) wife is able to keep herself, and (4) getting honesty from wife.